Evaluation of Three Blended Learning Courses to Strengthen Health Professionals' Capacity in Primary Health Care, Management of Sexual and Reproductive Health Services and Research Methods in Guinea - Millimouno, Tamba Mina; Delvaux, Thérèse; Kolié, Jean Michel; Kourouma, Karifa; Van Bastelaere, Stefaan; Tsunami, Carlos Kiyan; Béavogui, Abdoul Habib; Garcia, Marlon; Van Damme, Wim; Delamou, Alexandre (Frontiers in Digital Health, 2022)
Background Three blended courses on Primary Health Care (eSSP), Management of Sexual and Reproductive Health Services (eSSR), and Research Methods (eMR) were developed and implemented between 2017 and 2021 by the Maferinyah National Training and Research Center in Rural Health, a training and research institution of the Ministry of Health in Guinea. The study objectives were to evaluate the reasons for dropout and abstention, the learners' work behavior following the training, and the impact of the behavior change on the achievements of learners' organizations or services. Methods We evaluated the three implemented courses in 2021, focusing on levels 3 and 4 of the Kirkpatrick training evaluation model. Quantitative and qualitative data were collected through an open learning platform (Moodle), via an electronic questionnaire, during the face-to-face component of the courses (workshops), and at learners' workplaces. Descriptive statistics and thematic analysis were performed for quantitative and qualitative data, respectively. Results Out of 1,016 applicants, 543 including 137 (25%) women were enrolled in the three courses. Over the three courses, the completion rates were similar (67–69%) along with 20–29% dropout rates. Successful completion rates were 72% for eSSP, 83% for eMR and 85% for eSSR. Overall success rate (among all enrollees) ranged from 50% (eSSP) to 58% (eSSR). The majority (87%) of the learners reported applying the knowledge and skills they acquired during the courses through activities such as supervision (22%), service delivery (20%), and training workshops (14%). A positive impact of the training on utilization/coverage of services and increased revenues for their health facilities were also reported by some trainees. Conclusion These findings showed fair success rates and a positive impact of the training on learners' work behavior and the achievements of their organizations.